2021
DOI: 10.1111/pce.14049
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic plasticity of a tropical tree species, Tabebuia rosea, in response to elevated temperature and [CO2]

Abstract: Atmospheric and climate change will expose tropical forests to conditions they have not experienced in millions of years. To better understand the consequences of this change, we studied photosynthetic acclimation of the neotropical tree species Tabebuia rosea to combined 4°C warming and twice‐ambient (800 ppm) CO2. We measured temperature responses of the maximum rates of ribulose 1,5‐bisphosphate carboxylation (VCMax), photosynthetic electron transport (JMax), net photosynthesis (PNet), and stomatal conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 80 publications
2
14
2
Order By: Relevance
“…Each point represents an individual tree, solid lines are significant relationships (p < 0.05), and dotted lines are nonsignificant relationships. Hall et al, 2013;Kumarathunge et al, 2019;Yamaguchi et al, 2016), even in tropical tree species (Slot et al, 2021). Contrary to our results, previous studies have also shown decreasing A opt with increasing T optA due to performance tradeoffs in the underlying processes (Berry & Bjorkman, 1980;Dusenge, Wittemann, et al, 2021;Slot et al, 2021;, although in a meta-analysis Way and Yamori (2014) demonstrated that acclimation of T optA does not correspond to a consistent response in A opt across 103 species, possibly related to a cross-biome pattern of reduced ability to acclimate towards the (Crous, 2019;Crous et al, 2018).…”
Section: Photosynthetic Thermal Optima Do Not Acclimate To Different ...contrasting
confidence: 99%
See 3 more Smart Citations
“…Each point represents an individual tree, solid lines are significant relationships (p < 0.05), and dotted lines are nonsignificant relationships. Hall et al, 2013;Kumarathunge et al, 2019;Yamaguchi et al, 2016), even in tropical tree species (Slot et al, 2021). Contrary to our results, previous studies have also shown decreasing A opt with increasing T optA due to performance tradeoffs in the underlying processes (Berry & Bjorkman, 1980;Dusenge, Wittemann, et al, 2021;Slot et al, 2021;, although in a meta-analysis Way and Yamori (2014) demonstrated that acclimation of T optA does not correspond to a consistent response in A opt across 103 species, possibly related to a cross-biome pattern of reduced ability to acclimate towards the (Crous, 2019;Crous et al, 2018).…”
Section: Photosynthetic Thermal Optima Do Not Acclimate To Different ...contrasting
confidence: 99%
“…In addition, the activation state of Rubisco in most trees across all the study species did not significantly limit A net , and individuals in which Rubisco limitation was observed at high temperatures did not have significantly reduced A opt . This result is similar to some observations on the tropical tree Tabebuia rosea (Slot et al, 2021) and various herbaceous species (Sage et al, 2008), but contrary to other results showing significant high-temperature…”
Section: Photosynthetic Thermal Optima Do Not Acclimate To Different ...supporting
confidence: 91%
See 2 more Smart Citations
“…Perez et al (2021) found that high heat tolerance of PSII was associated with species that were thermal generalists, thus providing a proxy for evaluating the thermal niche of plants, while Slot, Cala, et al (2021) showed that PSII heat tolerance varies in a predictable way with site temperature and elevation. The ability to acclimate CO 2 uptake rates to higher temperatures is often related to shifts in the thermal sensitivity and capacity of photosynthetic processes, and can occur quite quickly (Slot, Rifai, & Winter, 2021).…”
Section: Carbon Dynamics As a Key Regulator Of Plant Heat Stress Responsesmentioning
confidence: 99%